PENERAPAN MODEL DISCOVERY LEARNING DALAM PEMBELAJARAN BAHASA INDONESIA BERORIENTASI KEARIFAN LOKAL DI SEKOLAH DASAR - Sugiyatmi, Sugiyatmi; Nugrahani, Farida; Suwarto, Suwarto (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2026)
This study aims to describe the application of the discovery learning model in Indonesian learning that is oriented to local wisdom, constraints, and solutions. Data collection was carried out by observation, interviews, and document analysis. Data sources come from teachers, students, learning processes, and teaching materials. The location of the research is at SD Negeri 05 Karangrejo, Kerjo District, Karanganyar Regency. This study uses a descriptive qualitative method through a study approach based on a single case. Data is in the form of information related to the implementation, utilization, constraints, and learning solutions with the discovery learning model. Validation of research data using triangulation methods and member checks. Data analysis is carried out using an interactive model: data reduction, data presentation, and conclusion drawing. The results of the study show that the application of the discovery learning model is able to create a more interesting, relevant, and contextual learning experience. Students become more active in exploring the material, understanding linguistic concepts more deeply, and having a high appreciation for the local culture. The discovery learning model encourages students to think critically about material related to local culture and traditions. Some of the obstacles found in the implementation of learning are; limited internet facilities, limited time available, and differences in the level of student involvement in the process of finding information. Its implementation has several obstacles, but the benefits obtained are much greater, especially in creating more meaningful learning for students.